Anchored guided rehabilitation - Minal Sanjay Kumthekar; Pronob Kumar Sanyal; Shivsagar Tewary (Wolters Kluwer Medknow Publications, 2020)
The loss of mandibular continuity leads to difficulty in swallowing, problems in mastication, altered mandibular movement, impaired speech articulation, and cosmetic disfigurement. Rehabilitation of such patients becomes more challenging in the case of complete edentulous maxillary and mandibular arches due to a lack of support and anchorage. This case report describes prosthetic rehabilitation of completely edentulous arches with segmental mandibulectomy. Hence, the anchorage was provided with the help of osseointegrated implants in both the maxillary and mandibular arches. Deviation of the mandible toward the unresected side during mastication and other functions was corrected using a palatal ramp. An attempt was made for prosthetic rehabilitation of mandibulectomy defect which required a multidisciplinary approach and which fulfilled the patient's requirement of mastication.